2022
DOI: 10.1021/acs.inorgchem.2c02211
|View full text |Cite
|
Sign up to set email alerts
|

Ni(II)-Incorporated Porphyrin-Based Conjugated Porous Polymer Derived from 2,6-Diformyl-4-methylphenol as a Catalyst for the Urea Oxidation Reaction

Abstract: The urea oxidation reaction (UOR) is an excellent alternative to the sluggish oxygen evolution reaction (OER) as an anode reaction for hydrogen generation via electrochemical water splitting. Here, a porphyrin-based conjugated porous polymer (CPP) has been developed through the polycondensation reaction of 2,6-diformyl-4-methylphenol and pyrrole (DMP-POR). The nickel(II) complex of this conjugated polymer Ni-DMP-POR shows efficient UOR in an alkaline medium. The as-synthesized materials were characterized by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…The position of the phenyl carbons is observed at ∼130 ppm. The small peak centered at 158 ppm may be attributed to the α-carbon of the pyrrole unit. To analyze the morphology of Cu-TEG-POR, FESEM (Figure a) and TEM (Figure b) analyses were performed. The SEM (Figure a) and TEM (Figure b) images show the morphology of Cu-TEG-POR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The position of the phenyl carbons is observed at ∼130 ppm. The small peak centered at 158 ppm may be attributed to the α-carbon of the pyrrole unit. To analyze the morphology of Cu-TEG-POR, FESEM (Figure a) and TEM (Figure b) analyses were performed. The SEM (Figure a) and TEM (Figure b) images show the morphology of Cu-TEG-POR.…”
Section: Resultsmentioning
confidence: 99%
“…The higher stability helps to organize the individual porphyrin moieties, which could increase the specific surface area of Cu-TEG-POR. 66,69 Thermogravimetric analysis was done to evaluate the thermal stability of TEG-POR and Cu-TEG-POR (Figure S6a). Both TEG-POR and Cu-TEG-POR show excellent stability up to 400 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cao et al showed OER and ORR activities of metal-corrole-based POP . There are other examples, where researchers have put efforts into designing some noble metal-based catalysts. In our recent efforts to explore the catalytic activity of porphyrin-based polymers, we have reported a urea oxidation reaction (UOR) and nonenzymatic glucose sensing using metal-incorporated porphyrin-based polymers.…”
Section: Introductionmentioning
confidence: 99%